Exploring Art Education: A Comparative Analysis of English and Finnish Curricula with Recommendations for Curriculum Enhancement - Kotilainen, Jedi (My University, 2024)
This qualitative study investigates the differences between English and Finnish primary school art curricula, aiming to explore different approaches to teaching art. Despite differences in schooling systems, notably the two-year head start for English children and the limited use of standardised testing compared to Finland, both nations face challenges with declining art education, despite its recognised value. Using a framework analysis methodology, data were collected from the curricula of each country. The curriculum is a multifaceted document where the instructional contents are written. This study specifically focuses on the written curriculum, excluding other aspects such as the hidden curriculum. Many English educators have described the English art curriculum as being outdated and too short. On the other hand, the objectives outlined in the Finnish art curriculum are considered appropriately defined. In English art education, the curriculum is characterised by a minimal number of objectives and a pronounced focus on art history. It adequately guides what students should use to create art but is ambiguous how art should be analysed. Contrastingly, the Finnish curriculum offers a broader variety of content, predominantly well-articulated, yet it overlooks the significance of art history. It includes objectives that prioritise multisensory, working skills, values, and sustainable development, aspects absent from the English curriculum. However, the Finnish curriculum does lack specificity in guiding students on art production methods. Based on these findings, I proposed several recommendations for what an effective primary school art curriculum should consist of. I advocated that the curriculum’s objectives should be diverse and comprehensive. Clear and concise instructional guidelines should be provided to facilitate effective and unified teaching methods while allowing educators the flexibility to incorporate their own approaches. Moreover, integrating art history into the curriculum is essential as it can inspire students and enhance their cultural awareness.
Keywords: art education, English, Finnish, curriculum, objectives, recommendations